THE DEPENDENCE OF THE INTERNAL STRESSES LEVEL IN THE ELEMENTS OF RAILWAY AXLES FROM THE REGIMES OF STRENGTHENING TREATMENT - Vakulenko, I. O.; Hryshchenko, M. A.; Perkov, O. M. (Science and Transport Progress, 2008)
The differential cooling of railway wheels parts affects the change of the wheel stress state.